Revaluasi Aset Tetap Kapal dan Implikasinya terhadap Pengenaan Pajak Penghasilan Final pada Perusahaan Pelayaran - Ahmad Rosyid Karomi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study analyzes the impact of fixed asset revaluation on corporate income tax liabilities in the domestic shipping sector. The background of this research is based on the importance of accurate fixed asset valuation in tax calculations, particularly for assets subject to value fluctuations, such as ships. The objective of this study is to identify the difference between the book value and the revalued value of ship fixed assets, and to analyze its implications for tax liabilities. This research uses a quantitative approach with descriptive analysis methods, utilizing secondary data from the financial statements of PT. ABC as a case study. The Wilcoxon signed-rank test was used to test the significant difference between the book value and the revalued value of assets. The results show a significant difference between the book value and the revalued value of PT. ABC's ship assets, resulting in an increase in tax liabilities. This research has significant implications for companies in implementing proper accounting practices and complying with applicable tax regulations, as well as for tax authorities in improving supervision and tax compliance.